The development of ecumenical thought on economic issues, 1920-1970. - Aoanan, Melanio LaGuardia ([Manila] : Southeast Asia Graduate School of Theology, 1973)
The problem of this study is to examine one area of the churches' practical concerns: economic issues. More and more, economic issues have been recognized as legitimate areas of concern of church life. The church cannot maintain her indifference towards these concerns and at the same time pretend to be faithful to Christ; for Christ is the Lord not only of the church but of the whole of life, including the economic sphere.
In partial fulfillment of the requirements for the degree Master of Theology (S.E.A.)
A thesis presented to the Southeast Asia Graduate School of Theology
Thesis (M.Theo.) - the South East Asia Graduate School of Theology
Keywords: Christianity and economics; Missions and Christian union